Exploring How Nigerian Banks Regulators Enforce Compliance with the Code of Corporate Governance - Aderonke, Tayo-Tiwo (European Scientific Journal, ESJ, 2020)
Frequent bank failures in Nigeria, resulting in enormous losses of investments and jobs, have raised questions about the banks’ compliance with the code of corporate governance. This single exploratory qualitative case study focused on the regulators of banks in Nigeria, the CBN, to find out the problems they may be encountering. Purposeful sampling was used to select 25 participants, and data were collected through Semistructured interviews. The agency theory served as the conceptual framework. Findings showed that the CBN had put measures in place to ensure full compliance. Some of which included the installation of robust IT architecture, the recruitment of highly skilled IT personnel, in-depth monthly e-examinations of the banks, application of steep penalties, enforcement of the omnibus clause, and continuous staff training. Findings revealed in this paper show that the Central Bank of Nigeria had implemented several measures that would forestall future bank failures among Nigerian banks.